1981
DOI: 10.1002/jcp.1041090213
|View full text |Cite
|
Sign up to set email alerts
|

The synthesis of protein(S) for chromosome condensation may be regulated by a post‐transcriptional mechanism

Abstract: A temperature sensitive mutant of BHK21, tsBN2, showed a premature chromosome condensation (PCC) upon the temperature shift of 40.5 degrees, even in the absence of DNA replication. The induction of PCC requires new protein synthesis, but not necessarily new RNA synthesis. Our data suggested that the messenger RNA for chromosome condensation starts to be transcribed at the beginning of S phase. At the permissive temperature (33.5 degrees), the messenger RNA for chromosome condensation translated with a very slo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
54
0

Year Published

1985
1985
2007
2007

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 25 publications
4
54
0
Order By: Relevance
“…The finding that protein-synthesis inhibitors prevent both PCC-induction and an activation of p34cdc kinase caused by tsBN2-mutation (Nishimoto et al, 1981;Ajiro and Nishimoto, 1985;Nishitani et al, 1991) indicates that the protein(s) synthesized by loss of RCC1 function is essential for an activation of p34cdc2 kinase. So far, two proteins, cyclin B and cdc25 have been known to be required for an activation of p34cdc2 kinase (Nurse, 1990).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The finding that protein-synthesis inhibitors prevent both PCC-induction and an activation of p34cdc kinase caused by tsBN2-mutation (Nishimoto et al, 1981;Ajiro and Nishimoto, 1985;Nishitani et al, 1991) indicates that the protein(s) synthesized by loss of RCC1 function is essential for an activation of p34cdc2 kinase. So far, two proteins, cyclin B and cdc25 have been known to be required for an activation of p34cdc2 kinase (Nurse, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…to the nonpermissive one (Nishimoto et al, , 1981Nishitani et al, 1991). In this mutant, therefore, a negative feedback control ensuring a coupling between S and M phases is defective at the nonpermissive temperature.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…For the induction of chromosome condensation, new protein but not DNA synthesis is required, thereby suggesting that a chromosome-condensing protein(s) is produced in tsBN2 cells as a result of the temperature shift. With premature condensation of the chromosome, tsBN2 cells cease to proliferate and die (9,10). Thus, using tsBN2 cells as a recipient of DNA-mediated gene transfer, a eucaryotic gene required for the regulatory process of chromosome condensation could be cloned.…”
mentioning
confidence: 99%
“…Our results are too preliminary to attribute the stimulation to complementation, although they are consistent with this possibility. It has been suggested that the mutation in ts BN-2 affects DNA initiation (1,8) and chromosome condensation (4,8,9). The system described herein provides the potential for identification of the factors and perhaps of the genes involved in these important biological processes.…”
mentioning
confidence: 99%